Quantifying the split-elbow sign: a comprehensive study in amyotrophic lateral sclerosis - He, Sheng-Yi; Cai, Wei-Chen; Su, Wei-Ming; Duan, Qing-Qing; Jiang, Zheng; Yin, Kang-Fu; Gu, Xiao-Jing; Chen, Yong-Ping; Cao, Bei (Frontiers in Neurology, 2024)
PurposeThe split-elbow sign (SES), characterized by preferential dysfunction of the biceps brachii compared to the triceps, is a clinical feature observed in amyotrophic lateral sclerosis (ALS). However, the quantified SES index has not been extensively investigated, and its role in diagnosing ALS remains unknown. Therefore, this study aimed to investigate the split-elbow index (SEI) derived from compound muscle action potential (CMAP), motor unit number index (MUNIX), and echo intensity (EI) in ALS.MethodsA cohort comprising 70 individuals diagnosed with ALS, along with 41 disease controls and 40 healthy controls, was recruited for the study. The SEI was calculated by dividing the recorded values of CMAP, MUNIX, and EI obtained over the biceps brachii by the corresponding value measured in the triceps, resulting in SEICMAP, SEIMUNIX, and SEIEI, respectively. Receiver operating characteristic (ROC) curves of the three methods were used for comparison. Statistical analyses were performed using SPSS V.26.0 and R software.ResultsBoth SEICMAP and SEIMUNIX exhibited significant reductions in ALS patients compared to that in controls (PSEICMAp < 0.0001, PSEIMUNIX < 0.0001), while SEIEI showed an elevation (P < 0.0001). Furthermore, there was a notable decrease in SEIMUNIX values as the disease progressed (p < 0.001). Moreover, ROC for SEIMUNIX exhibited superior diagnostic performance (AUC = 0.846), and a comprehensive diagnostic approach combining SEICMAP, SEIMUNIX, and SEIEI resulted in AUC (0.90) on the ROC curve.ConclusionOur study suggested that SES has emerged as a significant clinical characteristic in ALS and indicated the potential of SES indicators as biomarkers for both diagnosis and assessment of disease progression in ALS.